Injury patterns and risk factors in high school futsal: An observational study - Rafif Jendra Atmaja (CV Rezki Media, 2025)
Background: Sports injuries at an early age are crucial and must be given attention. Objectives: This study aims to analyze injury patterns, causative factors, and prevention strategies specific to high school futsal players. Methods: The research method used was descriptive quantitative with a cross-sectional study approach. The population in this study were male students of State Senior High School 1 Ponorogo who participated in class meeting activities, with purposive sampling technique found 24 samples. Data collected by questionnaire included information on the type of injury, location of injury, causative factors, injury treatment and type of rehabilitation. Results: The results showed that the most common injuries were cuts/abrasions (29%) and bruises (23%), most common in the lower extremities, namely knees (23%) and ankles (20%), the most common cause of injury was physical contact (54%), most injuries occurred during the second half (67%), the most common first aid given was cold compresses (51%) and the most common rehabilitation/therapy was massage (25%) and physiotherapy (21%). Conclusions: The findings can be concluded that the most dominant type of injury experienced by students is abrasion, especially in the knee area. In addition, the main causative factors of injury are fatigue, infrastructure, and collisions between players. The results of this study indicate the urgency of implementing injury prevention programs and the importance of conducting post-injury rehabilitation, in an effort to minimize the risk of injury to support the sustainability of students' careers in sports.